CYBER NOTARY AND THE PRINCIPLE OF TABLELIONIST OFFICIUM FIDELITER EXERCEBO - Patricia Jessica; Fully Handayani Ridwan (Faculty of Law, Universitas Pekalongan, 2023)
The development of technology forces humans to keep updated with the digital technology. At first the buying and selling transactions have been affected the digital technology and then continuous to service provisions in the notarial field. A cyber notary is a new service that creates electronic deeds on behalf of a notary and serves as an authentic deed. However, there are difficulties in putting it into action because of the Civil Code's Law No.2 of 2014 jo.Law no.30 of 2004 regarding the Notary Position and Law No.11 of 2008 regarding conflicting information and electronic transactions. As the authority of the notary to make authentic deeds is viewed from the perspective of the Civil Code, Law no. 1, it is necessary to investigate this issue so that, in the future, the application of the cyber notary does not conflict with the principle of the tablelionis officium fideliter exercebo. Law No. 11 of 2008 regarding Electronic Transactions and Information and Law No.2 of 2014 regarding the Notary Position.This study is important because it shows that a cyber notary can help notaries carry out their responsibilities more effectively. Considering the current technology developments have developed rapidly, synchronization of relevant laws and regulations is also needed.Keywords : Authentic Deed, Cyber Notary, tablelionis officium fideliter exercebo, notary